Association of personality profiles with coping and adjustment to cancer among patients undergoing chemotherapy. Issue 6 (22nd March 2020) - Langford, Dale J.; Morgan, Stefana; Cooper, Bruce; Paul, Steven; Kober, Kord; Wright, Fay; Hammer, Marilyn J.; Conley, Yvette P.; Levine, Jon D.; Miaskowski, Christine; Dunn, Laura B.
Abstract: Objective: Specific personality traits are associated with differential use of various coping strategies. Few studies have examined the relationship between personality and coping in oncology patients undergoing chemotherapy. We, therefore, examined the relationship between previously identified personality profiles (ie, Distressed [14.3% of total sample], Normative [53.8%], Resilient [31.9%]) and measures of coping and adjustment. Methods: Patients (n = 1248) undergoing chemotherapy for breast, gastrointestinal, gynecological, or lung cancer completed measures of personality (NEO‐Five Factor Inventory), coping (Brief COPE), and psychological adjustment to cancer (Mental Adjustment to Cancer [MAC] scale). Differences in coping and adjustment among the three personality profiles were evaluated using analysis of variance. Results: On the Brief COPE, the Distressed class endorsed lower use of Active Coping, Positive Reframing, Acceptance, Emotional Support (ie, "engagement" coping); and greater use of Denial, Venting, Behavioral Disengagement, Self‐Blame (ie, "disengagement" coping) compared to the Normative and Resilient classes. On the MAC scale, the Distressed class scored higher on Anxious Preoccupation, Helplessness/Hopelessness, Fatalism, and Avoidance, and lower on Fighting Spirit, compared to the other two classes. Conclusions: In this sample of oncology patients receiving chemotherapy, patients in the Distressed personality class showed a reduced repertoire of adaptive coping strategies, while those in the Resilient class reported greater use of adaptive or engagement coping strategies. Further work should examine the potential mediating or moderating role of coping and adjustment in the relationships between personality and patient outcomes. Interventions to enhance beneficial and reduce harmful coping strategies in cancer patients should be evaluated.